HUBUNGAN DISIPLIN DAN MOTIVASI KERJA GURU DENGAN PRESTASI BELAJAR SISWA SMP NEGERI DI KECAMATAN KETANGGUNGAN KABUPATEN BREBES - Piharsih, Piharsih; Ruhita, Ruhita (Edum Journal, 2021)
Abstract-Educational operations in educational units have several objectives that must be achieved, especially at the level of basic education which will become the foundation for continuing education. The main objective is student achievement. High student learning achievement is one indicator of the quality of education. Many things are thought to have a relationship with student achievement. Among others, discipline and teacher work motivation. Therefore, the focus of this study is to determine the degree of relationship between teacher discipline and work motivation with student achievement, both individually and simultaneously. The research method used is descriptive and verification methods, with data collection techniques using a Likert scale questionnaire, to 60 teachers. Processing of research results using regression analysis techniques. The significance test used the F-test. The results showed that: (1) There is a positive and significant relationship between teacher work discipline and student achievement. (2) There is a positive and significant relationship between teacher work motivation and student achievement. (3) There is a positive and significant relationship between work discipline and teacher work motivation (together) simultaneously with student achievement. Starting from these conditions the authors suggest: (1) The results of the study have shown that operationally there is a significant relationship between teacher work discipline and student achievement. This means that improving the conditions of teacher work discipline can encourage increased student achievement. The condition of teacher work discipline based on the respondent's assessment is in a good category, except that discipline towards the rules is very good. The author suggests that to encourage the improvement of student achievement, so that time discipline and responsibility are increased through exemplary and tightened supervision from the principal. (2) According to the results of the study, the teacher work motivation factor also has a relationship with student achievement. According to the respondent's assessment, the work motivation of teachers is in the very good category, except for the aspects of the motivation and understanding of the teacher's school goals. Therefore, to maximize student learning achievement, it is recommended to increase the motivation for the teacher through clear job descriptions and involve the teacher in setting school goals so that the teacher becomes more aware of the goals that the school must achieve.